Trattamento delle lesioni ossee traumatiche con le BMPs: revisione della letteratura - Tamini, J.; Tangredi, B.; Mazzacane; Marin, R.; Fazzari, F.; Stissi, P.; Pin, D.; Zappalà, G.; Castelnuovo, N.; Ronga, M. (Lo Scalpello - Journal, 2019)
TREATMENT OF TRAUMATIC BONE INJURIES WITH BMPS: A REVIEW OF THE LITERATUREThe treatment of open fractures and fracture non-unions is a challenging situation for the orthopaedic surgeon. Theuse of bone morphogenetic proteins (BMPs) in the treatment of these injuries has been assessed by several authors.Indicated for the treatment of open tibial fractures treated with intramedullary fixation and for the treatment oftibial long-bone non-union, BMPs nowadays have been tested in other anatomical sites. Although the clinical efficacyin these cases has not been demonstrated definitely, the use of BMPs has also been considered on the basis of its highcost. This review summarises the evidence present in the literature on BMPs for the treatment of open fractures andnon-unions.